Explore Role of Alkali Cations in Self-Assembly of Thorium Sulfate Complexes - LU Huang-jie; WANG Jian-qiang; LIN Jian (He huaxue yu fangshe huaxue, 2022)
The self-assembly of thorium complexes can be largely affected by ligand, while the role of alkali cations in the self-assembly requires further exploration. In this work, a series of thorium sulfate complexes were obtained by adding different alkali metal cations in the reactions, showing that alkali cations play a significant role in determining the topology and the hydrolysis product of thorium complexes. Single crystal X-ray diffraction analyses reveal that the incorporations of K+ and Cs+ ions result in a series of thorium sulfate structures with different dimensionalites, which include 1D chain, 2D layered network, and 3D frameworks. The larger Cs+ ion promotes the formation of two-dimensional layered topology and a rare ［Th3(μ3-O)］10+ trimeric polynuclear center. Rather than playing an innocent role in directing the structure, this work shows that alkali counterions affect both the overall topology and the nucleation of affording complexes.